Polypropylene-based high-strength antibacterial composite material and preparation method thereof

By introducing wood fiber modified reinforcing material and nano-silver synergistic quaternary ammonium salt antibacterial material into polypropylene material, the problems of bacterial growth and insufficient mechanical strength of polypropylene material during use are solved, achieving high strength and long-lasting antibacterial effect.

CN121045684APending Publication Date: 2025-12-02JIEYANG JUXIAN PLASTIC PROD CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202511329547.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-17
Publication Date
2025-12-02

AI Technical Summary

Technical Problem

Polypropylene materials are prone to bacterial growth during use and have insufficient mechanical strength. Existing antibacterial agents are inefficient and have poor long-term stability, which limits their application in some fields.

Method used

By adding wood fiber-modified reinforcing materials and nano-silver synergistic quaternary ammonium salt antibacterial materials to polypropylene, and combining with a specific process, high-strength antibacterial composite materials are prepared, thereby improving the mechanical properties and antibacterial effects of the materials.

Benefits of technology

It significantly improves the mechanical and antibacterial properties of polypropylene materials, achieves long-lasting antibacterial effects, and enhances the overall performance of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121045684A_ABST
    Figure CN121045684A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of polypropylene materials, in particular to a polypropylene-based high-strength antibacterial composite material and a preparation method thereof.Polypropylene, a wood fiber modified reinforcing material and a nano-silver synergistic quaternary ammonium salt antibacterial material are blended, so that the multiple advantages of high strength and antibacterial property are achieved; wherein the wood fiber modified reinforced material is prepared by modifying carboxyl-terminated liquid nitrile rubber with wood fibers and then grafting N-(2, 3-epoxypropyl)-phthalimide, the wood fibers have high strength and rigidity, the carboxyl-terminated liquid nitrile rubber has flexibility, and the N-(2, 3-epoxypropyl)-phthalimide has good mechanical properties. A benzene ring structure of 1, 3-epoxypropyl)-phthalimide can increase the rigidity of a molecular chain, so that the strength and toughness of polypropylene are improved, the nano-silver and quaternary ammonium salt synergistic antibacterial material is prepared by loading nano-silver on quaternary ammonium salt functionalized porous resin, quaternary ammonium salt and nano-silver synergistically resist bacteria, and the porous structure slows down the dissolution rate of nano-silver, so that the antibacterial effect of the nano-silver and quaternary ammonium salt synergistic antibacterial material is improved. The efficient and long-term antibacterial effect is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polypropylene materials technology, specifically to a high-strength antibacterial composite material based on polypropylene and its preparation method. Background Technology

[0002] Polypropylene (PP) possesses excellent corrosion resistance, insulation, mechanical properties, stability, and processability, making it widely used in furniture, household goods, plastics, building materials, small appliances, and automotive parts. While PP boasts relatively superior overall performance, its performance requirements are increasing with its wider applications, revealing its inherent limitations. Firstly, PP lacks antibacterial properties, making it susceptible to bacterial contamination during use. Secondly, PP suffers from insufficient mechanical strength. These shortcomings significantly restrict its application in some plastic products, such as water supply and drainage pipes. These pipes, coming into contact with water, are highly susceptible to bacterial growth. Since PP itself lacks antibacterial properties, bacteria cannot be eliminated promptly, posing a significant threat to human health. Therefore, performance improvements to PP are crucial for its effective application.

[0003] Physical blending antibacterial technology is the current mainstream technology. For example, the invention patent with application number CN202510664421.2 discloses a high-strength antibacterial composite material based on polypropylene and its preparation method. By using arginine antibacterial agent to modify polypropylene, the strength and antibacterial properties of polypropylene material are improved. Although arginine antibacterial agent has good compatibility with polypropylene material, its effect on improving the mechanical properties of polypropylene material is small. Moreover, arginine antibacterial agent has problems such as low sterilization efficiency and poor long-term stability. Therefore, it is necessary to improve the mechanical properties of polypropylene material and improve the problems of insufficient sterilization efficiency and inability to provide long-term antibacterial effect in polypropylene composite materials, so as to avoid the risks of using polypropylene materials in daily life or industrial fields. Summary of the Invention

[0004] The purpose of this invention is to provide a high-strength antibacterial composite material based on polypropylene and its preparation method.

[0005] The objective of this invention can be achieved through the following technical solutions:

[0006] A high-strength antibacterial composite material based on polypropylene, comprising the following raw materials in parts by weight:

[0007] 50-70 parts polypropylene, 2-5 parts wood fiber modified reinforcing material, 1-3 parts nano silver synergistic quaternary ammonium salt antibacterial material, 10-12 parts talc, 0.3-0.5 parts nucleating agent, 1-3 parts antioxidant.

[0008] Furthermore, the preparation method of the wood fiber modified and reinforced material specifically includes the following steps:

[0009] Step 1: Soak wood fibers in a 10-20% sodium hydroxide solution for 48-50 hours, filter, rinse, air dry at room temperature, and then place them in an oven at 75-85℃ for 11-13 hours for later use.

[0010] The second step involves adding wood fibers to N,N-dimethylformamide and ultrasonically dispersing them to obtain a uniform dispersion. Then, terminal carboxyl liquid nitrile rubber with a molecular weight of 5000-6000 and catalyst a are added to the dispersion. After stirring and mixing, heating is turned on to raise the temperature to 110-120℃. Stirring is continued at this temperature for 6-9 hours. After heating is stopped, the material is cooled and discharged to obtain terminal carboxyl liquid nitrile rubber modified wood fibers.

[0011] The third step involves adding N,N-dimethylformamide to the carboxyl-terminated liquid nitrile rubber-modified wood fiber, ultrasonically dispersing it evenly, then adding catalyst b and N-(2,3-epoxypropyl)-phthalimide, heating to 90-100℃, stirring for 7-9 hours, and centrifuging to obtain the wood fiber-modified reinforced material after the reaction is complete.

[0012] Furthermore, in the first step, the wood fiber is one of poplar wood fiber, paper mulberry wood fiber, eucalyptus wood fiber, sycamore wood fiber, pine wood fiber, locust wood fiber, or jujube wood fiber.

[0013] Furthermore, in the second step, catalyst a is p-toluenesulfonic acid or aminosulfonic acid.

[0014] Furthermore, in the third step, catalyst b is tetrabutylammonium bromide or benzyltriethylammonium chloride.

[0015] The above technical solution involves first immersing wood fibers in a sodium hydroxide solution to expose more hydroxyl groups on their surface. Then, through catalyst a and heating, the hydroxyl groups on the wood fiber surface and the carboxyl groups at one end of the carboxyl-terminated liquid nitrile rubber undergo an esterification reaction to obtain carboxyl-terminated liquid nitrile rubber-modified wood fibers. Finally, under the action of catalyst b and high temperature, the epoxy groups of N-(2,3-epoxypropyl)-phthalimide undergo a ring-opening addition reaction with the carboxyl groups of the carboxyl-terminated liquid nitrile rubber-modified wood fibers, thereby branching N-(2,3-epoxypropyl)-phthalimide molecules into the carboxyl-terminated liquid nitrile rubber-modified wood fibers, resulting in a modified and reinforced wood fiber material.

[0016] Furthermore, the preparation method of the nano-silver synergistic quaternary ammonium salt antibacterial material specifically includes the following steps:

[0017] A1. Add functional monomers, styrene, dilauryl peroxide and toluene to a reaction vessel and stir to form a uniform mixture. Set aside. Add polyvinyl alcohol to deionized water and stir to form a uniform mixture. Add the mixture to the reaction vessel and purge with nitrogen gas. React at 60-90℃ for 12-15 hours. Cool, filter, wash with anhydrous ethanol, and dry for 23-25 ​​hours to obtain quaternary ammonium salt functionalized porous resin.

[0018] A2. Add quaternary ammonium salt functionalized porous resin to deionized water, stir and disperse evenly, then add 0.01-0.03 mol / L silver nitrate solution and stir continuously for 1-2 hours. Then add glucose and stir at 75-85℃ for 7-9 hours. After centrifugation, separate the solid material, and then wash and dry it to obtain nano-silver synergistic quaternary ammonium salt antibacterial material.

[0019] Furthermore, in A1, the preparation method of the functional monomer includes the following steps:

[0020] Add bis(2-hydroxyethyl)dimethylammonium chloride to N,N-dimethylformamide and stir until homogeneous to obtain a mixed solution. Then add isocyanate methacrylate and dibutyltin dilaurate to the mixed solution, heat to 65-75℃, and stir at a constant temperature for 24-26 hours to obtain the functional monomer.

[0021] Using the above technical solution, dilauroyl peroxide is used as an initiator to initiate a cross-linking polymerization reaction between functional monomers and styrene. Toluene is used as a pore-forming agent to obtain a quaternary ammonium salt functionalized porous resin. In this process, the hydroxyl groups in bis(2-hydroxyethyl)dimethylammonium chloride and the isocyanate groups in isocyanate methacrylate undergo a polyurethane reaction under the influence of a catalyst and heating to obtain a functional monomer that has both cross-linking properties and contains quaternary ammonium salt. Subsequently, silver ions generated by nitrate ionization flow into the pores of the quaternary ammonium salt functionalized porous resin and are immobilized in the pores. By using glucose as a reducing agent, the silver ions are reduced to nano-silver, thus obtaining a nano-silver synergistic quaternary ammonium salt antibacterial material.

[0022] Furthermore, the nucleating agent is Millad3988 or DMDBS.

[0023] Furthermore, the antioxidant is antioxidant CA or antioxidant 1010.

[0024] A method for preparing a high-strength antibacterial composite material based on polypropylene includes the following steps:

[0025] Step 1: Add polypropylene, wood fiber modified reinforcing material, nano silver synergistic quaternary ammonium salt antibacterial material, talc, nucleating agent and antioxidant to a mixer and stir evenly at a speed of 1500-1700 r / min to obtain a premix.

[0026] Step 2: Feed the premixed material into the twin-screw extruder through the feed hopper. The extruder speed is 1100-1500 r / min, the feed speed is 1000-1200 r / min, and the extruder heating temperature is set to 190-210℃ in zone 1, 180-200℃ in zone 2, and 180-190℃ in zone 3. Extrusion is then carried out to obtain the composite material.

[0027] The beneficial effects of this invention are:

[0028] 1) The wood fiber modified reinforcing material prepared in this invention is obtained by modifying the surface of wood fibers with carboxyl-terminated liquid nitrile rubber and then grafting N-(2,3-epoxypropyl)-phthalimide. Wood fibers have high strength and high rigidity, which can effectively improve the strength of polypropylene. The rubber molecular chain has excellent flexibility, which can improve the toughness of wood fibers. The benzene ring structure of N-(2,3-epoxypropyl)-phthalimide can restrict the rotation of single bonds, increase the rigidity of molecular chains, and further enhance the strength and toughness of polypropylene. The carboxyl-terminated liquid nitrile rubber can also improve the compatibility between wood fibers and polypropylene, improve the interfacial bonding strength, and make stress more effectively transferred from the matrix to the wood fiber modified reinforcing material, thereby improving the mechanical properties of polypropylene composite materials.

[0029] 2) The nano-silver synergistic quaternary ammonium salt antibacterial material prepared by the present invention is obtained by loading nano-silver onto porous resin functionalized with quaternary ammonium salt. The quaternary ammonium salt functional groups can synergistically interact with nano-silver, giving the polypropylene composite material broad-spectrum antibacterial properties. Moreover, after being coated, the nano-silver can slow down its own dissolution rate, so that the composite material has high efficiency and long-term antibacterial properties.

[0030] Of course, any product implementing this invention does not necessarily need to achieve all of the advantages described above at the same time. Detailed Implementation

[0031] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0032] Example 1

[0033] A high-strength antibacterial composite material based on polypropylene, comprising the following raw materials in parts by weight:

[0034] 50 parts polypropylene, 2 parts wood fiber modified reinforcing material, 1 part nano silver synergistic quaternary ammonium salt antibacterial material, 10 parts talc, 0.3 parts Millad3988, and 1 part antioxidant CA.

[0035] The preparation method of the composite material includes the following steps:

[0036] Step 1: Add polypropylene, wood fiber modified reinforcing material, nano silver synergistic quaternary ammonium salt antibacterial material, talc, Millad3988 and antioxidant CA into a mixer and stir evenly at a speed of 1500 r / min to obtain a premix.

[0037] Step 2: Feed the premixed material into the twin-screw extruder through the feed hopper. The extruder speed is 1100 r / min, the feed speed is 1000 r / min, and the extruder heating temperature is set to 190℃ in zone 1, 180℃ in zone 2, and 180℃ in zone 3. Extrusion is then carried out to obtain the composite material.

[0038] The preparation method of wood fiber modified and reinforced materials specifically includes the following steps:

[0039] Step 1: Add 5.11g of wood fiber to 100ml of 20% sodium hydroxide solution, soak for 12 hours, filter, rinse, air dry at room temperature, and then put it in an oven to dry at 80℃ for 12 hours for later use.

[0040] Step 2: Take 4.21g of wood fiber and add it to 500ml of N,N-dimethylformamide. Disperse it by ultrasonication to obtain a uniform dispersion. Then add 7.16g of 6000 molecular weight end-carboxyl liquid nitrile rubber and 0.34g of p-toluenesulfonic acid to the dispersion. After stirring and mixing, turn on the heater and raise the temperature to 120℃. Stir continuously at this temperature for 8 hours. Then stop the heating, cool down and discharge the material to obtain end-carboxyl liquid nitrile rubber modified wood fiber.

[0041] Third step: Take 3.02g of carboxyl-terminated liquid nitrile rubber modified wood fiber and add it to 500ml of N,N-dimethylformamide. Disperse it evenly by ultrasonication. Then add 0.15g of tetrabutylammonium bromide and 0.10g of N-(2,3-epoxypropyl)-phthalimide. Heat to 130℃ and continue stirring for 8h. After the reaction is completed, separate by centrifugation to obtain the wood fiber modified reinforcement material.

[0042] The preparation method of the nano-silver synergistic quaternary ammonium salt antibacterial material specifically includes the following steps:

[0043] A1. Take 50.03g of functional monomer, 8.11g of styrene, 0.34g of dilauryl peroxide and 30ml of toluene and add them to the reaction vessel. Stir to form a uniform mixture and set aside. Then take 20ml of polyvinyl alcohol and add it to 180ml of deionized water. Stir well and add it to the mixed solution. Purge with nitrogen gas and react at 70℃ for 12h. Cool, filter, wash with anhydrous ethanol, and dry for 24h to obtain quaternary ammonium salt functionalized porous resin.

[0044] A2. Take 0.61g of quaternary ammonium salt functionalized porous resin and add it to 50ml of deionized water. After stirring and dispersing evenly, add 10ml of 0.02mol / L silver nitrate solution and continue stirring for 1.5h. Then add 30.14g of glucose and stir at 80℃ for 8h. After centrifugation, separate the solid material, wash and dry it to obtain nano-silver synergistic quaternary ammonium salt antibacterial material.

[0045] The preparation method of the functional monomer includes the following steps:

[0046] 1.48 g of bis(2-hydroxyethyl)dimethylammonium chloride was added to 50 ml of N,N-dimethylformamide and stirred until a mixed solution was obtained. Then, 1.27 g of isocyanate methacrylate and 0.82 g of dibutyltin dilaurate were added to the mixed solution, heated to 70 °C, and stirred at a constant temperature for 24 h to obtain the functional monomer.

[0047] Example 2

[0048] A high-strength antibacterial composite material based on polypropylene, comprising the following raw materials in parts by weight:

[0049] 60 parts polypropylene, 3 parts wood fiber modified reinforcing material, 2 parts nano silver synergistic quaternary ammonium salt antibacterial material, 11 parts talc, 0.4 parts Millad3988, and 2 parts antioxidant CA.

[0050] The preparation method of the high-strength antibacterial composite material of polypropylene includes the following steps:

[0051] Step 1: Add polypropylene, wood fiber modified reinforcing material, nano silver synergistic quaternary ammonium salt antibacterial material, talc, Millad3988 and antioxidant CA into a mixer and stir evenly at a speed of 1600 r / min to obtain a premix.

[0052] Step 2: Feed the premixed material into the twin-screw extruder through the feed hopper. The extruder speed is 1200 r / min, the feed speed is 1100 r / min, and the extruder heating temperature is set to 200℃ in zone 1, 190℃ in zone 2, and 185℃ in zone 3. Extrusion is then carried out to obtain the composite material.

[0053] The preparation methods of the wood fiber modified reinforcing material and the antibacterial agent are the same as in Example 1.

[0054] Example 3

[0055] A high-strength antibacterial composite material based on polypropylene, comprising the following raw materials in parts by weight:

[0056] 70 parts polypropylene, 5 parts wood fiber modified reinforcing material, 3 parts nano silver synergistic quaternary ammonium salt antibacterial material, 12 parts talc, 0.5 parts Millad3988, and 3 parts antioxidant CA.

[0057] The preparation method of the high-strength antibacterial composite material of polypropylene includes the following steps:

[0058] Step 1: Add polypropylene, wood fiber modified reinforcing material, nano silver synergistic quaternary ammonium salt antibacterial material, talc, Millad3988 and antioxidant CA into a mixer and stir evenly at a speed of 1700 r / min to obtain a premix.

[0059] Step 2: Feed the premixed material into the twin-screw extruder through the feed hopper. The extruder speed is 1500 r / min, the feed speed is 1200 r / min, and the extruder heating temperature is set to 210℃ in zone 1, 200℃ in zone 2, and 190℃ in zone 3. Extrusion is then carried out to obtain the composite material.

[0060] The preparation methods of the wood fiber modified reinforcing material and the antibacterial agent are the same as in Example 1.

[0061] Comparative Example 1

[0062] A high-strength antibacterial composite material based on polypropylene, comprising the following raw materials in parts by weight:

[0063] 60 parts polypropylene, 3 parts wood fiber, 2 parts nano silver synergistic quaternary ammonium salt antibacterial material, 11 parts talc, 0.4 parts Millad3988, and 2 parts antioxidant CA.

[0064] The preparation method of the high-strength antibacterial composite material of polypropylene includes the following steps:

[0065] Step 1: Add polypropylene, wood fiber, talc, Millad3988 and antioxidant CA to a mixer and stir evenly at a speed of 1600 r / min to obtain a premix.

[0066] Step 2: Feed the premixed material into the twin-screw extruder through the feed hopper. The extruder speed is 1200 r / min, the feed speed is 1100 r / min, and the extruder heating temperature is set to 200℃ in zone 1, 190℃ in zone 2, and 185℃ in zone 3. Extrusion is then carried out to obtain the composite material.

[0067] The preparation method of the antibacterial agent is the same as that in Example 1.

[0068] Comparative Example 2

[0069] A high-strength antibacterial composite material based on polypropylene, comprising the following raw materials in parts by weight:

[0070] 60 parts polypropylene, 2 parts nano silver synergistic quaternary ammonium salt antibacterial material, 11 parts talc, 0.4 parts Millad3988, and 2 parts antioxidant CA.

[0071] The preparation method of the high-strength antibacterial composite material of polypropylene includes the following steps:

[0072] Step 1: Add polypropylene, nano-silver synergistic quaternary ammonium salt antibacterial material, talc, nucleating agent and antioxidant to a mixer and stir evenly at a speed of 1600 r / min to obtain a premix.

[0073] Step 2: Feed the premixed material into the twin-screw extruder through the feed hopper. The extruder speed is 1200 r / min, the feed speed is 1100 r / min, and the extruder heating temperature is set to 200℃ in zone 1, 190℃ in zone 2, and 185℃ in zone 3. Extrusion is then carried out to obtain the composite material.

[0074] The preparation method of the antibacterial agent is the same as that in Example 1.

[0075] Comparative Example 3

[0076] A high-strength antibacterial composite material based on polypropylene, comprising the following raw materials in parts by weight:

[0077] 60 parts polypropylene, 3 parts wood fiber modified reinforcing material, 2 parts nano silver, 11 parts talc, 0.4 parts Millad3988, and 2 parts antioxidant CA.

[0078] The preparation method of the high-strength antibacterial composite material of polypropylene includes the following steps:

[0079] Step 1: Add polypropylene, wood fiber modified reinforcing material, nano silver, talc, Millad3988 and antioxidant CA into a mixer and stir evenly at a speed of 1600 r / min to obtain a premix.

[0080] Step 2: Feed the premixed material into the twin-screw extruder through the feed hopper. The extruder speed is 1200 r / min, the feed speed is 1100 r / min, and the extruder heating temperature is set to 200℃ in zone 1, 190℃ in zone 2, and 185℃ in zone 3. Extrusion is then carried out to obtain the composite material.

[0081] The preparation method of the wood fiber modified and reinforced material is the same as that in Example 1.

[0082] Performance testing

[0083] The high-strength antibacterial polypropylene composite materials from Examples 1-3 and Comparative Examples 1-3 of this invention were prepared into test strips that met various tests, and the following performance tests were conducted:

[0084] Tensile property test:

[0085] Tensile properties were tested in accordance with GB / T1040.1-2025 "Determination of tensile properties of plastics" using an RGT-20 electronic universal testing machine with a tensile rate of 10 mm / min and a sensor of 500 N. Five replicates were tested in each group and the average value was taken.

[0086] Antibacterial test:

[0087] Antimicrobial properties were determined according to GB / T31402-2015 "Test Method for Antimicrobial Properties of Plastic Surfaces". Gram-negative bacteria were used as typical test strains. The antimicrobial efficacy of the samples was systematically evaluated. After the activated bacterial suspension was inoculated into the culture medium, it was cultured in a constant temperature shaker at 37℃, and then centrifuged and resuspended in phosphate buffered saline. The bacterial concentration was calibrated to 1×10⁻⁶. 7 CFU / ml, dilute the bacterial solution at a ratio of V bacteria:V culture medium = 6:1000, take 100μL of the diluted bacterial solution and evenly drop it onto the sample surface, ensuring that the bacterial solution completely covers the sample, and incubate in a constant temperature shaker at 37℃ for 24h. Use 4ml of PBS buffer to wash the bacteria on the sample surface to form a bacterial solution dilution, take the bacterial solution dilution to 100CFU / ml, and then take 50μL of the diluted bacterial solution and evenly spread it on a solid culture medium plate. Incubate in a constant temperature shaker at 37℃ for 24h, count the colonies, calculate the inhibition rate, and design a blank experiment as a control group;

[0088] Formula for calculating antibacterial rate: X=(A0-A1) / A0×100%

[0089] Where: A0: Colony count in the control group;

[0090] A1: Corresponding measured values ​​for the experimental group.

[0091] Sustained-release properties:

[0092] Place the dialysis bag containing 5ml of sample into 500ml of deionized water and stir magnetically at 35℃. After 5 days, measure the concentration of nano-silver in the deionized water.

[0093] The experimental results are shown in the table below:

[0094] Tensile strength / MPa Elongation at break / % Antibacterial rate / % Nano silver concentration / % Example 1 38.9 4.3 99.5 23.7 Example 2 43.1 5.1 99.9 22.3 Example 3 39.6 4.8 99.7 23.5 Comparative Example 1 21.3 2.9 99.3 23.9 Comparative Example 2 10.4 1.1 99.1 24.2 Comparative Example 3 38.0 4.3 81.2 67.8

[0095] According to the table above, no reinforcing material was added in Comparative Example 2. Combined with the addition of wood fiber in Comparative Example 1, it can be seen that wood fiber enhances the mechanical properties of polypropylene. In Examples 1-3 and Comparative Example 3, the wood fiber surface was modified with carboxyl-terminated liquid nitrile rubber, improving the compatibility between wood fiber and polypropylene and increasing the interfacial bonding strength. Simultaneously, the carboxyl-terminated liquid nitrile rubber molecular chain has flexibility, further enhancing the strength and toughness of polypropylene. The intracyclic structure in N-(2,3-epoxypropyl)-phthalimide can restrict the rotation of single bonds, increasing the rigidity of the molecular chain and more effectively improving the strength and toughness of polypropylene. In contrast, the wood fiber in Comparative Example 1 was not modified, resulting in a poor reinforcing effect. Combining the comparative examples and the examples, it can be concluded that the nano-silver synergistic quaternary ammonium salt antibacterial material has no significant impact on the mechanical properties of polypropylene.

[0096] As can be seen from the table above, the antibacterial effects of Examples 1-3 and Comparative Examples 1 and 2 are significantly higher than those of Comparative Example 3. This is because the quaternary ammonium salt functional groups on the surface of the antibacterial material have a synergistic effect with the nano-silver, giving the polypropylene composite material broad-spectrum antibacterial properties. Moreover, the nano-silver precipitation rate of other samples is much lower than that of Comparative Example 3. This is because the porous structure coating of nano-silver can slow down the dissolution rate of nano-silver, achieving a highly efficient and long-term antibacterial effect. In contrast, Comparative Example 3 only contains nano-silver, resulting in a poor sterilization effect.

[0097] The above description is merely an example and illustration of the concept of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described or use similar methods to replace them, as long as they do not deviate from the concept of the invention or exceed the scope defined in the claims, they should all fall within the protection scope of the present invention.

Claims

1. A high-strength antibacterial composite material based on polypropylene, characterized in that, The raw materials include the following parts by weight: 50-70 parts polypropylene, 2-5 parts wood fiber modified reinforcing material, 1-3 parts nano silver synergistic quaternary ammonium salt antibacterial material, 10-12 parts talc, 0.3-0.5 parts nucleating agent, and 1-3 parts antioxidant.

2. The high-strength antibacterial composite material based on polypropylene according to claim 1, characterized in that, The preparation method of the wood fiber modified and reinforced material specifically includes the following steps: Step 1: Soak wood fibers in a 10-20% sodium hydroxide solution for 12-16 hours, filter, rinse, air dry at room temperature, and then place them in an oven at 75-85℃ for 11-13 hours for later use. The second step involves adding wood fibers to N,N-dimethylformamide and ultrasonically dispersing them to obtain a uniform dispersion. Then, terminal carboxyl liquid nitrile rubber with a molecular weight of 5000-6000 and catalyst a are added to the dispersion. After stirring and mixing, heating is turned on to raise the temperature to 110-120℃. Stirring is continued at this temperature for 6-9 hours. After heating is stopped, the material is cooled and discharged to obtain terminal carboxyl liquid nitrile rubber modified wood fibers. The third step involves adding N,N-dimethylformamide to the carboxyl-terminated liquid nitrile rubber-modified wood fiber, ultrasonically dispersing it evenly, then adding catalyst b and N-(2,3-epoxypropyl)-phthalimide, heating to 90-100℃, stirring for 7-9 hours, and centrifuging to obtain the wood fiber-modified reinforced material after the reaction is complete.

3. The high-strength antibacterial composite material based on polypropylene according to claim 2, characterized in that, In the first step, the wood fiber is any one of poplar wood fiber, paper mulberry wood fiber, eucalyptus wood fiber, sycamore wood fiber, pine wood fiber, locust wood fiber, and jujube wood fiber.

4. The high-strength antibacterial composite material based on polypropylene according to claim 2, characterized in that, In the second step, catalyst a is p-toluenesulfonic acid or aminosulfonic acid.

5. The high-strength antibacterial composite material based on polypropylene according to claim 2, characterized in that, In the third step, catalyst b is tetrabutylammonium bromide or benzyltriethylammonium chloride.

6. The high-strength antibacterial composite material based on polypropylene according to claim 1, characterized in that, The preparation method of the nano-silver synergistic quaternary ammonium salt antibacterial material specifically includes the following steps: A1. Add functional monomers, styrene, dilauryl peroxide and toluene to a reaction vessel and stir to form a uniform mixture. Set aside. Add polyvinyl alcohol to deionized water and stir to form a uniform mixture. Add the mixture to the reaction vessel and purge with nitrogen gas. React at 60-90℃ for 12-15 hours. Cool, filter, wash with anhydrous ethanol, and dry for 23-25 ​​hours to obtain quaternary ammonium salt functionalized porous resin. A2. Add quaternary ammonium salt functionalized porous resin to deionized water, stir and disperse evenly, then add 0.01-0.03 mol / L silver nitrate solution and stir continuously for 1-2 hours. Then add glucose and stir at 75-85℃ for 7-9 hours. After centrifugation, separate the solid material, and then wash and dry it to obtain nano-silver synergistic quaternary ammonium salt antibacterial material.

7. The high-strength antibacterial composite material based on polypropylene according to claim 6, characterized in that, In A1, the preparation method of the functional monomer includes the following steps: Add bis(2-hydroxyethyl)dimethylammonium chloride to N,N-dimethylformamide and stir until homogeneous to obtain a mixed solution. Then add isocyanate methacrylate and dibutyltin dilaurate to the mixed solution, heat to 65-75℃, and stir at a constant temperature for 24-26 hours to obtain the functional monomer.

8. The high-strength antibacterial composite material based on polypropylene according to claim 1, characterized in that, The nucleating agent is Mild lad3988 or DMDBS.

9. The high-strength antibacterial composite material based on polypropylene according to claim 1, characterized in that, The antioxidant is antioxidant CA or antioxidant 1010.

10. A method for preparing a high-strength antibacterial composite material based on polypropylene as described in claim 1, characterized in that, The preparation method includes the following steps: Step 1: Add polypropylene, wood fiber modified reinforcing material, nano silver synergistic quaternary ammonium salt antibacterial material, talc, nucleating agent and antioxidant to a mixer and stir evenly at a speed of 1500-1700 r / min to obtain a premix. Step 2: Feed the premixed material into the twin-screw extruder through the feed hopper. The extruder speed is 1100-1500 r / min, the feed speed is 1000-1200 r / min, and the extruder heating temperature is set to 190-210℃ in zone 1, 180-200℃ in zone 2, and 180-190℃ in zone 3. Extrusion is then carried out to obtain the composite material.

Citation Information

Patent Citations

  • High-strength antibacterial polypropylene composite material and preparation method thereof

    CN120289916A

  • Natural-fiber-reinforced polypropylene composite material with mildewproof and antimicrobial properties and preparation method thereof

    CN105504501A

  • Chitosan-loaded nano-silver antibacterial polypropylene material and preparation method thereof

    CN110343327A

  • Synthesis process for catalyzing ethyl shikimic acid by cation exchange resin

    CN118580147A

  • Method for preparation of antibacterial bio-filler for plastic and antibacterial bio-filler for plastic prepared thereby

    US20220356308A1